A new species of Lathyrus L. (section Cicercula; Fabaceae) from Turkey - Genc, Hasan; Sahin, Ahmet (Oxford Univ Press, 2008)
A new species, Lathyrus egirdiricus H.Genc & A.Sahin (section Cicercula; Fabaceae), is described from Turkey, with illustrations and taxonomic comments. Characteristics of the species are compared with those of the related species Lathyrus hirsutus L., L. stenophyllus Boiss. & Heldr., L. sativus L., L. cassius Boiss. and L. gorgoni Parl., from which it differs mainly in the shape, length, width and venation of leaflets, length and width of the stipule, flower colour, legume and style length. (C) 2008 The Linnean Society of London.
Keywords: Leguminosae; taxonomy